Professor Marian Zembala (1950-2022) - Mariusz Gąsior; Zbigniew Kalarus; Piotr Przybyłowski (Termedia Publishing House, 2022)
Professor Marian Zembala, MD, PhD - an outstanding Polish cardiac surgeon and transplant surgeon, scientist, long-time academic teacher and educator of young people, director, and also a great lover of music, poetry, theater, painting, and sailing. He was born on February 11, 1950, in Krzepice near Częstochowa. He graduated from the Medical University of Wrocław in 1974 with honors and received the Primus Inter Pares award of the Polish Minister of Health, with a possibility to choose the place of work. He chose the Heart Surgery Department of the Medical Academy in Wrocław, which was his dream. Alongside his clinical work, he developed his scientific interests. In 1979, at the age of 29, he defended his doctorate with honors. His work in the Wrocław Clinic also provided an opportunity to go for his dream internship abroad, e.g. to the hospital in Utrecht, the Netherlands, where he worked under the supervision of Prof. F. Hitchcock (1981-1985). During his stay in the Netherlands, he initiated the largest post-World War II program of Polish Heart Poolse hartpatientjes naar Nederland, under which more than 500 Polish children with severe congenital heart defects were operated on free of charge between 1981 and 1992. For this ambitious project, he received an honorary award from Utrecht University and an award from the Primate of Poland, Cardinal Józef Glemp.